Sistem Pendukung Keputusan Pemilihan Perpanjangan Kontrak Kerja Karyawan dengan Metode SMART - Ignatius Joko Dewanto; Nur Aziz; Wahyu Darmawan (Yayasan Literasi Sains Indonesia, 2023)
Contract employees are one of the growing HR needs in the industry. The rapid need for contract employees makes HR leaders with the support of information systems still have difficulty in deciding the extension of contract employees according to their wishes. The research objective is a computerized program that is used to determine and evaluate special actions to determine the extension of contract employees using the Simple Multi Attribute Rating Technique (SMART) and Knowledge Data Discovery (KDD) methods. The research problem is to analyze and take into account the assessment of employees in carrying out their work through several criteria, then given the weighting, normalizing the weights, finally giving the parameter values ​​for each criterion. The system development method uses SDLC, the result of which is the application is a DSS that can decide through multiple criteria, while the criteria used are: discipline, attitude, potential and ability, work results and supporting factors. Research contributions assist the manufacturing resources department in determining the extension of contract employees. The output of the research is the application of a decision support system for the extension of contract employees, further research on the development of other DSS that can develop the company's human resource need.